2017
DOI: 10.1097/md.0000000000005768
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of yes-associated protein (YAP1) gene in polycystic ovary syndrome

Abstract: Background:DNA methylation modification has been proved to influence the phenotype of polycystic ovary syndrome (PCOS). Genome-wide association studies (GWAS) demonstrate that yes-associated protein (YAP1) genetic sites are associated with PCOS. The study aims to detect the methylation status of YAP1 promoter in ovary granulosa cells (GCs) of PCOS patients and explore novel therapeutic targets for PCOS.Methods:Randomized controlled trial was applied and a total of 72 women were included in the study, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Their study also indicated that the alleles are associated with insulin sensitivity and resistance and LH levels, further validating the association with clinical PCOS. Additionally, aberrancy in YAP1 methylation patterns among patients with PCOS has been demonstrated by Jiang et al [44]. Although our pilot study did not demonstrate differential expression of LATS1 among PCOS patients and controls, Sun et al [45] found that a deletion in Lats 1 resulted in ovarian germ cell apoptosis and follicular cysts.…”
Section: Resultssupporting
confidence: 45%
“…Their study also indicated that the alleles are associated with insulin sensitivity and resistance and LH levels, further validating the association with clinical PCOS. Additionally, aberrancy in YAP1 methylation patterns among patients with PCOS has been demonstrated by Jiang et al [44]. Although our pilot study did not demonstrate differential expression of LATS1 among PCOS patients and controls, Sun et al [45] found that a deletion in Lats 1 resulted in ovarian germ cell apoptosis and follicular cysts.…”
Section: Resultssupporting
confidence: 45%
“…Promoter hypermethylation of critical growth regulators like tumor suppressor genes and its subsequent transcription silencing plays a pivitol role in causing cancer [ 31 ]. A recent study demonstrated hypomethylation of YAP promoter promotes the expression of YAP in polycystic ovary syndrome [ 32 ]. However, methylation status of YAP promoter in breast cancer is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Among 257 participants, 124 fertile men were considered as controls and 133 were primary infertile men. Total participants were divided into different groups according to their smoking and/or drinking habits such as, fertile control subjectssmokers (29), alcohol drinkers (33), smokers+alcohol drinkers (34) and total abstainers (who never smoked or drank alcohol before 28), Infertile subjects-smokers (30), alcohol drinkers (34), smokers+alcohol drinkers (37) and total abstainers (32; fig. 1).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The male reproductive hormones in serum samples were measured using Cobas e411 analyser with platform electrochemiluminescence immunoassay technique (Roche Diagnostics, Mannheim, Germany) and the normal range for LH, FSH, testosterone, and prolactin hormones were 4-11 mIU/ml, 2-10 mIU/ml, 2-12 ng/ml and 2-18 ng/ml, respectively [29] .…”
Section: Semen Analysis Blood Collection Serum Separation and Hormomentioning
confidence: 99%